Physical, physiological, and tactical responses of U-15 and U-17 soccer players to numerically balanced and unbalanced small-sided games - Borges, E. D. P. A.; Praça, G. M.; Trombiero, D. S.; Guimarães, J. D. S.; Vieira, C. A.; Laporta, L.; Castro, H. D. O.; Lira, C. A. B. D.; Leonardi, T. J.; Costa, G. D. C. T. (Journal of Physical Education and Sport, 2024)
Small-sided games (SSGs) are commonly employed to simulate game-specific scenarios, emphasizing the importance of incorporating numerical equality and imbalance to mirror real match dynamics. This study evaluated the physical, physiological, and tactical responses of U-15 and U-17 soccer players during SSGs with numerical balance and numerical superiority in the offensive phase. The sample included 28 male athletes, with 14 from each age group participating in official competitions based on the national schedule. The SSGs were organized in 5v5 and 5v5+2 configurations, with each session consisting of four 6-minute bouts interspersed with 3-minute recovery periods. The sessions alternated between formats, with the first 6-minute period conducted as 5v5, followed by 5v5+2, and so on. On the second day of data collection, the order was reversed.